O composto BiFeO3-PbTiO3 Dopado com La : relações propriedade/estrutura - Freitas, Valdirlei Fernandes (2011)
In this work, the structural and physical properties of the (0.6)BiFeO3-(0.4)PbTiO3 + x% La compounds, synthesized by high-energy ball milling, were investigated as a function of La concentration for understanding the structure/property relations in these materials. The X-ray and neutron diffraction results revealed potentialities for performing structural tuning by adding La in these materials. In fact, a structural phase transition, from tetragonal to romboedral, as well as the coexistence of both symmetries for 3% of La, was observed with the increase of the La content. In fact, the Rietveld refinement analyses indicated that the romboedral phase changes from R3m to R3c for 5 % of La. The transmission electron microscopic studies revealed narrow ferroelectric domain-walls in tetragonal (90° domainswalls) and romboedral (180° domain-walls) symmetries. The morphotropic phase boundary, which would be the interface between two symmetries in a same particle, was not observed in the sample studied in this work. The time dependency of the electrical resistivity, i. e., the equilibrium electrical resistivity, was analyzed and the results reveal that the La doping controls the formation of charge carriers in these materials. The "electric polarization vectors", per unit cell, were determined by using the mean average position of the cations and anions, obtained from the Rietveld refinement, and indicated polarized unit cells for all studied compositions. However, only those samples with 3% and 5% of La showed a measurable macroscopic ferroelectric behavior. In summary, the whole set of results indicate a strong correlation between ferroic properties and structure in all studied samples, and that these correlations can be changed by atomic, chemical and structural changes promoted by the La doping. Finally, the determination of the magnetoelectric response suggests that these compounds can potentiality used in advanced technological applications in multifunctional devices.